STUDI KASUS KETERLAMBATAN BERBICARA ANAK USIA 5-6 TAHUN DI TK ISLAM TERPADU ROBBANI OGAN ILIR - Nuansyah Indah Putri; Windi Dwi Andika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the characteristics of speech delays in children aged 5–6 years at Robbani Integrated Islamic Kindergarten in Ogan Ilir. The study used a descriptive qualitative approach with a case study method, where the subject of the study was a boy with the initials AKA. Data collection was carried out through observation, interviews, and documentation, then analyzed using the Miles and Huberman model to obtain a detailed and accurate picture of the phenomenon. The results showed that AKA was starting to be able to combine one to two words with the help of stimuli, but was not yet able to construct meaningful sentences. He could pronounce simple words clearly, but had difficulty conveying simple sentences, feelings, and experiences verbally. He still showed limited two-way interaction, minimal initiative to start conversations, difficulty maintaining eye contact, and was more interested in objects or activities of interest. The child still had difficulty concentrating for long periods and required repetition to understand instructions, although he understood directions better when the teacher used demonstrations or pointed to objects. Based on these findings, the characteristics of children aged 5–6 years with speech delays can be categorized into three main aspects: language (limited vocabulary, difficulty pronouncing words and constructing sentences, difficulty expressing feelings), social-emotional (difficulty in social interaction, avoiding eye contact, using gestures in communication), and cognitive (difficulty focusing attention, requiring repetition, and being more interested in interesting things). These findings are expected to be a basis for teachers, parents, and early childhood education practitioners in designing appropriate learning strategies to support the language and communication development of children with speech delays.